Non-Ionizing (Ultra-Wideband Frequency) Electromagnetic Radiation Effect On Nerve Fiber Action Potential Of Human Body - Muhammad Syafiq, Noor Azizi; Azahari, Salleh; Adib, Othman; Nor Azlan, Mohd Aris; Najmiah Radiah, Mohamad; Maisarah, Abu; Nornikman, Hassan; Mohamad Hafize, Ramli (Penerbit UTM Press, 2016)
In modern telemedicine systems the physiological data of patients can be measured with the aid of electronic sensors located on and inside the human body. The collected medical data is then transmitted wirelessly to an external unit for processing, thereby enhancing the health monitoring, diagnosis, and therapy of the patients. In biomedical application, the process requires transmitting data, images and videos from inside the body taken by a radio system of a size of a pill seems to be the way. The use of non-ionizing electromagnetic radiation in various areas like medical application has arisen the electromagnetic radiation problem. The services provided by this type of application can cause either good or bad effects on human body depending on the power level, frequency and the way it being used. The implant antenna with ultra-wideband (UWB) frequency will be used by inserting it into the nerve of human arm in term of homogenous model. Ultra-wideband (UWB) is a wireless technology that potential applications in variety of medical areas such as implant wireless sensors, microwave hyperthermia, imaging and radar. It can transmit digital data over a wide frequency spectrum with very low power and at very high data rates. Hence, this paper present the non-ionizing electromagnetic radiation effect on electrical nerve fiber of human arm model with the presence of other human tissues such as fat, muscle, skin and etc. at ultra-wideband frequency which is expected to improve the understanding of radio propagation inside human body hence contribute to more advance and innovative medical implants. CST Microwave Studio is one of the EM modeling code which can be used for bio electromagnetic purpose.